A micro-nano core-shell structure metal oxide material, a preparation method and application thereof
Patent Information
- Application Number
- CN202610229063.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-26
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-02-26
AI Technical Summary
[0004]本申请的主要目的是提出一种微纳米核壳结构金属氧化物材料及其制备方法与应用,旨在解决或至少部分缓解现有的微纳米结构材料制备工艺复杂、可控性、可重复性差的问题
[0016] The method for preparing micro/nano core-shell structured metal oxide materials proposed in this application is simple and controllable, using inexpensive and readily available raw materials. Triethanolamine possesses multiple functions including complexation, guidance, and pore formation, eliminating the need for additional structure-directing or pore-forming agents. Furthermore, the assembly of porous micro/nano composite core-shell structures from nanoscale components as building blocks is achieved through only two steps: hydrothermal reaction and heat treatment. This eliminates the need for templates and toxic reagents, significantly simplifying the process and reducing equipment requirements, making it suitable for industrial scale-up.
Smart Images

Figure CN122212273B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of nanomaterial synthesis and preparation technology, and in particular to a micro / nano core-shell structured metal oxide material and its preparation method and application. Background Technology
[0002] Nanostructured materials have attracted much attention due to their superior lithium storage performance (compared to traditional bulk electrode materials). This performance improvement stems from the shortening of the lithium storage space created by the nanostructure. + This increases the diffusion distance and the contact area between the electroactive material and the electrolyte. However, nanostructured materials still suffer from rapid capacity decay, mainly due to severe self-aggregation caused by their high surface energy, and the Li... + The specific volume changes of nanoparticles during the insertion / extraction process. Regarding the first question, micro / nanostructured materials with porous microstructures (composed of nanoscale subunits) are considered an ideal choice for electrode materials.
[0003] Existing methods for preparing micro / nanostructured materials with porous microstructures often employ template methods and multi-step hydrothermal / solvothermal methods, which rely on complex equipment and toxic chemical reagents. These methods are complex, have poor controllability, and poor reproducibility. Therefore, there is an urgent need to develop a simple, controllable, highly reproducible, and high-performance method for preparing micro / nanostructured materials. Summary of the Invention
[0004] The main purpose of this application is to propose a micro / nano core-shell structured metal oxide material, its preparation method and application, aiming to solve or at least partially alleviate the problems of complex, uncontrollable and poor reproducibility of existing micro / nano structured material preparation processes.
[0005] To achieve the above objectives, in a first aspect, this application proposes a method for preparing micro / nano core-shell structured metal oxide materials, comprising:
[0006] A precursor solution is prepared by dissolving a metal source containing nickel ions, manganese ions, and cobalt ions, urea, and triethanolamine in a solvent and mixing them. The precursor solution was subjected to a hydrothermal reaction to obtain a precursor precipitate; The precursor precipitate was subjected to heat treatment to obtain the micro / nano core-shell structured metal oxide material.
[0007] In some embodiments, the molar ratio of nickel ions, manganese ions, and cobalt ions in the metal source is 1:(0.8~1.2):(3.5~4.5).
[0008] In some embodiments, the molar ratio of cobalt ions to urea is 1:(0.033~0.1), and 2~6 g of urea is added per 100 mL of water.
[0009] In some embodiments, the amount of triethanolamine added is 8 to 10 mL of triethanolamine per 100 mL of water.
[0010] In some embodiments, the hydrothermal reaction is carried out at a temperature of 160-200°C for 2-4 hours.
[0011] In some embodiments, the heat treatment temperature is 500~700℃, the heating rate is 2~10℃ / minute, and the time is 4~10 hours.
[0012] In some embodiments, the heat treatment process further includes the following steps: The precursor precipitate is then cleaned and dried.
[0013] Secondly, this application proposes a micro / nano core-shell structured metal oxide material prepared using the preparation method provided in the first aspect of this application. The micro / nano core-shell structured metal oxide material has a core-shell structure and a hierarchical porous structure.
[0014] In some embodiments, the micro / nano core-shell structured metal oxide material is a ternary metal oxide with the chemical formula Ni. x Mn 1-x Co2O4, where 0 <x<1。
[0015] Thirdly, this application proposes the application of a micro / nano core-shell structured metal oxide material prepared by the preparation method proposed in the first aspect of this application, and the application of the micro / nano core-shell structured metal oxide material proposed in the second aspect of this application in the preparation of anodes for alkali metal ion batteries.
[0016] The method for preparing micro / nano core-shell structured metal oxide materials proposed in this application is simple and controllable, using inexpensive and readily available raw materials. Triethanolamine possesses multiple functions including complexation, guidance, and pore formation, eliminating the need for additional structure-directing or pore-forming agents. Furthermore, the assembly of porous micro / nano composite core-shell structures from nanoscale components as building blocks is achieved through only two steps: hydrothermal reaction and heat treatment. This eliminates the need for templates and toxic reagents, significantly simplifying the process and reducing equipment requirements, making it suitable for industrial scale-up.
[0017] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described below. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0019] Figure 1 X-ray diffraction pattern of the black powder product prepared in Example 1 provided for the embodiments of this application; Figure 2 Scanning electron microscope image of the black powder product prepared in Example 1, which is provided as an embodiment of this application; Figure 3 X-ray energy dispersive spectroscopy (EDS) pattern of the black powder product prepared in Example 1, which is provided as an embodiment of this application; Figure 4 Transmission electron microscopy (TEM) image of the black powder product prepared in Example 1, which is provided as an embodiment of this application; Figure 5 A high-resolution transmission electron microscope image of the black powder product prepared in Example 1, provided as an embodiment of this application; Figure 6 The N2 adsorption-desorption isotherm and BJH pore size distribution diagram of the black powder product prepared in Example 1 provided for the embodiments of this application; Figure 7 The charge-discharge cycle performance curves of a lithium-ion battery using the black powder product prepared in Example 1 as the negative electrode, provided as an embodiment of this application; Figure 8 A rate performance curve of a lithium-ion battery using the black powder product prepared in Example 1 as the negative electrode, provided as an embodiment of this application; Figure 9 Scanning electron microscope (SEM) images of the black powder products prepared in Examples 1 and 2 and Comparative Examples 1 to 4, provided for the embodiments of this application; Figure 10 Scanning electron microscope image of the black powder product prepared in Comparative Example 5, which is provided as an embodiment of this application; Figure 11 X-ray energy dispersive spectroscopy (EDS) pattern of the black powder product prepared in Comparative Example 5, which is provided as an embodiment of this application. Figure 12 Transmission electron microscopy image of the black powder product prepared in Comparative Example 5, which is provided as an embodiment of this application; Figure 13 A high-resolution transmission electron microscope image of the black powder product prepared in Comparative Example 5, which is provided as an embodiment of this application.
[0020] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0021] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0022] It should be noted that if the embodiments of this application involve directional indicators (such as up, down, left, right, front, back, etc.), the directional indicators are only used to explain the relative positional relationship and movement of the components in a specific posture. If the specific posture changes, the directional indicators will also change accordingly.
[0023] Furthermore, if the embodiments of this application involve descriptions such as "first" or "second," these descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, the use of "and / or" or "and / or" throughout the text includes three parallel solutions. For example, "A and / or B" includes solution A, solution B, or a solution that simultaneously satisfies A and B. Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed in this application.
[0024] Based on the above problems, in a first aspect, embodiments of this application propose a method for preparing micro / nano core-shell structured metal oxide materials, comprising: S1. Dissolve a metal source containing nickel ions, manganese ions and cobalt ions, urea and triethanolamine in water and mix to obtain a precursor solution; S2. The precursor solution is subjected to a hydrothermal reaction to obtain the precursor precipitate; S3. The precursor precipitate is subjected to heat treatment to obtain the micro / nano core-shell structured metal oxide material.
[0025] The preparation method provided in this application requires only two steps: hydrothermal reaction and heat treatment. It eliminates the need for templates, multi-step reactions, and toxic reagents, enabling the preparation of micro / nano core-shell structured metal oxide materials. The equipment requirements are low, making it suitable for large-scale production. Triethanolamine simultaneously possesses a triple function of complexation, guidance, and pore formation. Specifically, the nitrogen and hydroxyl oxygen atoms in triethanolamine can react with Ni²⁺. + Mn² + Co² + The formation of stable complexes controls the release rate of metal ions, preventing amorphous aggregates caused by rapid precipitation and laying the foundation for subsequent ordered assembly. Simultaneously, the selective adsorption of triethanolamine on different crystal planes induces anisotropic growth, promoting the directional stacking of primary nanoparticles to form a heterogeneous structure with a dense core and a loose outer shell. Finally, the triethanolamine decomposes during heat treatment, releasing gas and leaving vacancies, forming a mesoporous / macroporous network in situ. This allows for fabrication without additional templates or etching steps.
[0026] In some embodiments, the molar ratio of nickel ions, manganese ions, and cobalt ions in the metal source is 1:(0.8~1.2):(3.5~4.5). For example, the molar ratio of nickel ions, manganese ions, and cobalt ions in the metal source is 1:0.8:3.5, 1:1:4, or 1:1.2:4.5, etc.
[0027] Setting the nickel, manganese, and cobalt ions in the metal source to this ratio ensures that the final micro / nano core-shell structured metal oxide material has the target morphology.
[0028] In some embodiments, the molar ratio of cobalt ions to urea is 1:(0.033~0.1), and 2~6 g of urea is added per 100 mL of water. For example, the molar ratio of cobalt ions to urea is 1:0.033, 1:0.05, 1:0.08, or 1:0.1, etc. 2 g, 3 g, 4 g, 5 g, or 6 g of urea can be added per 100 mL of water, etc.
[0029] Too low a urea dosage (molar ratio < 0.033) fails to provide sufficient precipitant, resulting in incomplete metal ion precipitation and low precursor yield. Conversely, too high a urea dosage (molar ratio > 0.1) leads to excessively rapid hydrolysis, instantly generating numerous precipitate nuclei, causing severe particle agglomeration and uncontrolled particle size distribution. By controlling the urea dosage within the aforementioned range, the precipitation reaction kinetics can be precisely adjusted, ensuring a mild, continuous, and uniform nucleation and growth process. This results in precursor particles with uniform size and regular morphology, providing an ideal template for the precise construction of subsequent core-shell structures.
[0030] In some embodiments, the amount of triethanolamine added is 8 to 10 mL per 100 mL of water. For example, 8 mL, 9 mL, or 10 mL of triethanolamine is added per 100 mL of water.
[0031] The amino and hydroxyl groups in triethanolamine molecules can form five-membered ring chelates with transition metal ions. These chelates have a moderate complexation stability constant (lgK≈6~8), effectively inhibiting early hydrolysis of metal ions while ensuring gradual release of metal ions under hydrothermal conditions, thus achieving kinetic control of the precipitation process. Furthermore, as a nonionic surfactant, triethanolamine can selectively adsorb onto specific crystal planes, inducing precursor particles to grow along specific orientations through steric hindrance, promoting the self-assembly of core-shell structures. When the addition amount is less than 8 mL, the complexation and morphology regulation effects are insufficient; when it exceeds 10 mL, the system viscosity becomes too high and organic residue increases, negatively impacting product purity and structural regularity.
[0032] In some embodiments, the hydrothermal reaction temperature is 160-200°C, and the reaction time is 2-4 hours. For example, the hydrothermal reaction temperature is 160°C, 170°C, 180°C, 190°C, or 200°C, etc. The hydrothermal reaction time is 2 hours, 2.5 hours, 3 hours, 3.5 hours, or 4 hours, etc.
[0033] If the hydrothermal reaction temperature is below 160℃, urea hydrolysis is slow, the reaction system has low supersaturation, insufficient nucleation driving force, and the products are mostly amorphous or incompletely crystallized flocculent precipitates. If the hydrothermal reaction temperature is above 200℃, the hydrolysis rate is too fast, and the high temperature intensifies Ostwald ripening, leading to particle coarsening and blurred core-shell interfaces. By limiting the hydrothermal reaction time to 2-4 hours, the precipitation reaction can be fully carried out and over-ripening can be avoided, ensuring that the extracted particles have a clear core-shell morphology and suitable particle size, thus guaranteeing the maintenance of the micro-nano-scale core-shell structure after heat treatment.
[0034] In some embodiments, the heat treatment temperature is 500~700℃, the heating rate is 2~10℃ / min, and the time is 4~10 hours. For example, the heat treatment temperature is 500℃, 550℃, 600℃, 650℃, or 700℃, etc. The heating rate is 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, or 10℃ / min, etc. The heat treatment time is 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours, etc.
[0035] If the heat treatment temperature is below 500℃, the organic components (amine groups, carbonate groups, etc.) in the precursor will not decompose completely, and the spinel phase will have low crystallinity and insufficient electrochemical activity. If the heat treatment temperature is above 700℃, the grains will grow rapidly (>1 μm), the specific surface area will decrease sharply, and the core-shell structure may collapse due to violent grain boundary migration and rapid gas release.
[0036] In some embodiments, step S3, prior to heat treatment, further includes cleaning and drying the precursor precipitate. Specifically, the precursor precipitate is cleaned sequentially with deionized water and ethanol, followed by drying under vacuum at 60°C for 12 hours. Cleaning with deionized water or ethanol and drying remove soluble impurities from the surface of the precursor precipitate, providing a basis for subsequent heat treatment.
[0037] This application also proposes a micro / nano core-shell structured metal oxide material prepared by the method described above. The micro / nano core-shell structured metal oxide material has a core-shell structure and a hierarchical porous structure.
[0038] In some embodiments, the micro / nano core-shell structured metal oxide material is a ternary metal oxide with the chemical formula Ni. x Mn 1-x Co2O4, where 0 <x<1。
[0039] This application also provides a micro / nano core-shell structured metal oxide material prepared by the method described above, and its application in the preparation of alkali metal ion batteries. Preferably, the micro / nano core-shell structured metal oxide material is used to prepare electrodes for alkali metal ion batteries.
[0040] The following specific examples provide further details.
[0041] Example 1 Nickel acetate tetrahydrate (Ni(CH3COO)2·4H2O, 0.25 mmol), manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O, 0.25 mmol), cobalt acetate tetrahydrate (Co(CH3COO)2·4H2O, 1.0 mmol), urea (CO(NH2)2, 4.0 g), and triethanolamine (TEA, 8 mL) were added to 100 mL of deionized water and magnetically stirred for 2 hours until completely dissolved. The solution was then transferred to a 100 mL PTFE-lined stainless steel autoclave, sealed, and maintained at 180°C for 2.5 hours. After the hydrothermal reaction, the product was collected from the autoclave, washed sequentially with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 hours. Subsequently, the sample was heated to 600°C in air at a heating rate of 5°C / min and calcined for 8 hours. The final product obtained is a black powder (labeled as NMCO-8), which is a micro / nano core-shell structured metal oxide material.
[0042] Example 2 Nickel acetate tetrahydrate (Ni(CH3COO)2·4H2O, 0.25 mmol), manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O, 0.25 mmol), cobalt acetate tetrahydrate (Co(CH3COO)2·4H2O, 1.0 mmol), urea (CO(NH2)2, 4.0 g), and triethanolamine (TEA, 10 mL) were added to 100 mL of deionized water and magnetically stirred for 2 hours until completely dissolved. The solution was then transferred to a 100 mL PTFE-lined stainless steel autoclave, sealed, and maintained at 180°C for 2.5 hours. After the hydrothermal reaction, the product was collected from the autoclave, washed sequentially with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 hours. Subsequently, the sample was heated to 600°C in air at a heating rate of 5°C / min and calcined for 8 hours. The final product obtained is a black powder (labeled as NMCO-10), which is a micro / nano core-shell structured metal oxide material.
[0043] Example 3 Nickel acetate tetrahydrate (Ni(CH3COO)2·4H2O, 0.25 mmol), manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O, 0.3 mmol), cobalt acetate tetrahydrate (Co(CH3COO)2·4H2O, 1.125 mmol), urea (CO(NH2)2, 2.0 g), and triethanolamine (TEA, 8 mL) were added to 100 mL of deionized water and magnetically stirred for 2 hours until completely dissolved. The solution was then transferred to a 100 mL PTFE-lined stainless steel autoclave, sealed, and maintained at 160°C for 4 hours. After the hydrothermal reaction, the product was collected from the autoclave, washed sequentially with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 hours. Subsequently, the sample was heated to 700°C in air at a heating rate of 10°C / min and calcined for 4 hours. The final product obtained is a black powder, which is a micro / nano core-shell structured metal oxide material.
[0044] Example 4 Nickel acetate tetrahydrate (Ni(CH3COO)2·4H2O, 0.25 mmol), manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O, 0.2 mmol), cobalt acetate tetrahydrate (Co(CH3COO)2·4H2O, 0.875 mmol), urea (CO(NH2)2, 6.0 g), and triethanolamine (TEA, 9 mL) were added to 100 mL of deionized water and magnetically stirred for 2 hours until completely dissolved. The solution was then transferred to a 100 mL PTFE-lined stainless steel autoclave, sealed, and maintained at 200°C for 2 hours. After the hydrothermal reaction, the product was collected from the autoclave, washed sequentially with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 hours. Subsequently, the sample was heated to 500°C in air at a heating rate of 2°C / min and calcined for 10 hours. The final product obtained is a black powder, which is a micro / nano core-shell structured metal oxide material.
[0045] Comparative Example 1 Nickel acetate tetrahydrate (Ni(CH3COO)2·4H2O, 0.25 mmol), manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O, 0.25 mmol), cobalt acetate tetrahydrate (Co(CH3COO)2·4H2O, 1.0 mmol), urea (CO(NH2)2, 4.0 g), and triethanolamine (TEA, 2 mL) were added to 100 mL of deionized water and magnetically stirred for 2 hours until completely dissolved. The solution was then transferred to a 100 mL PTFE-lined stainless steel autoclave, sealed, and maintained at 180°C for 2.5 hours. After the hydrothermal reaction, the product was collected from the autoclave, washed sequentially with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 hours. Subsequently, the sample was heated to 600°C in air at a heating rate of 5°C / min and calcined for 8 hours. The final product was a black powder (labeled as NMCO-2).
[0046] Comparative Example 2 Nickel acetate tetrahydrate (Ni(CH3COO)2·4H2O, 0.25 mmol), manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O, 0.25 mmol), cobalt acetate tetrahydrate (Co(CH3COO)2·4H2O, 1.0 mmol), urea (CO(NH2)2, 4.0 g), and triethanolamine (TEA, 4 mL) were added to 100 mL of deionized water and magnetically stirred for 2 hours until completely dissolved. The solution was then transferred to a 100 mL PTFE-lined stainless steel autoclave, sealed, and maintained at 180°C for 2.5 hours. After the hydrothermal reaction, the product was collected from the autoclave, washed sequentially with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 hours. Subsequently, the sample was heated to 600°C in air at a heating rate of 5°C / min and calcined for 8 hours. The final product was a black powder (labeled as NMCO-4).
[0047] Comparative Example 3 Nickel acetate tetrahydrate (Ni(CH3COO)2·4H2O, 0.25 mmol), manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O, 0.25 mmol), cobalt acetate tetrahydrate (Co(CH3COO)2·4H2O, 1.0 mmol), urea (CO(NH2)2, 4.0 g), and triethanolamine (TEA, 6 mL) were added to 100 mL of deionized water and magnetically stirred for 2 hours until completely dissolved. The solution was then transferred to a 100 mL PTFE-lined stainless steel autoclave, sealed, and maintained at 180°C for 2.5 hours. After the hydrothermal reaction, the product was collected from the autoclave, washed sequentially with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 hours. Subsequently, the sample was heated to 600°C in air at a heating rate of 5°C / min and calcined for 8 hours. The final product was a black powder (labeled as NMCO-6).
[0048] Comparative Example 4 Nickel acetate tetrahydrate (Ni(CH3COO)2·4H2O, 0.25 mmol), manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O, 0.25 mmol), cobalt acetate tetrahydrate (Co(CH3COO)2·4H2O, 1.0 mmol), urea (CO(NH2)2, 4.0 g), and triethanolamine (TEA, 12 mL) were added to 100 mL of deionized water and magnetically stirred for 2 hours until completely dissolved. The solution was then transferred to a 100 mL PTFE-lined stainless steel autoclave, sealed, and maintained at 180°C for 2.5 hours. After the hydrothermal reaction, the product was collected from the autoclave, washed sequentially with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 hours. Subsequently, the sample was heated to 600°C in air at a heating rate of 5°C / min and calcined for 8 hours. The final product was a black powder (labeled NMCO-12).
[0049] Comparative Example 5 Manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O, 0.5 mmol), cobalt acetate tetrahydrate (Co(CH3COO)2·4H2O, 1.0 mmol), urea (CO(NH2)2, 4.0 g), and triethanolamine (TEA, 8 mL) were added to 100 mL of deionized water and magnetically stirred for 2 hours until completely dissolved. The solution was then transferred to a 100 mL PTFE-lined stainless steel autoclave, sealed, and maintained at 180°C for 2.5 hours. After the hydrothermal reaction, the product was collected from the autoclave, washed sequentially with deionized water and ethanol, and then dried in a vacuum oven at 60°C for 12 hours. Subsequently, the sample was heated to 600°C in air at a heating rate of 5°C / min and calcined for 8 hours. A black powder product (labeled MCO-8) was finally obtained.
[0050] The black powder product prepared in Example 1 was characterized using an X-ray diffractometer (XRD, Rigaku D / max-2200PC) equipped with Cu Kα radiation (λ = 0.15418 nm), with a scanning angle range of 10°–80°. The morphology and microstructure of the samples were observed using a field emission scanning electron microscope (FE-SEM, JEOL JSM-7500F) and a transmission electron microscope (TEM, JEOL JEM-2100F). The elemental composition of the samples was analyzed using an energy-dispersive X-ray spectrometer (EDS) mounted on the FE-SEM and an X-ray photoelectron spectrometer (XPS, AXIS ULTRA DLD) equipped with a Mg Kα–Al Kα dual-anode excitation source. The N2 adsorption-desorption performance of the samples was determined using an ASAP-2010 surface area analyzer, and the pore size distribution data was calculated from the isothermal adsorption curves. Specific results are as follows: Figure 1 For XRD test results, from Figure 1 As can be seen, the characteristic peaks of the NMCO-8 sample clearly show the superposition of the characteristic peak shapes of cubic phases MnCo2O4 (JCPDS No. 84-0482) and NiCo2O4 (JCPDS No. 73-1702), and no other impurity peaks were observed. Therefore, it can be preliminarily confirmed that the NMCO-8 product is a product of mixed MnCo2O4 and NiCo2O4 components.
[0051] Figure 2 For scanning electron microscope images, from Figure 2As can be seen, the scanning electron microscope (SEM) images of the NMCO-8 sample show that it has a uniform micron-sized particle morphology with a particle size of approximately 6 μm. Further magnified high-magnification SEM images reveal that individual NMCO particles exhibit an assembly structure formed by the rotation, stacking, and aggregation of cubic secondary structural units with sizes of approximately 0.5–1 μm, resembling an irregular Rubik's Cube. Further magnified images of the surface morphology of individual particles show that the sample surface has obvious porous characteristics, and this porous structure is assembled from nanoscale particles.
[0052] Figure 3 For X-ray energy spectrum scanning, from Figure 3 It can be seen that the NMCO-8 product is composed of Ni, Co, Mn, and O elements, and the Ni and Mn elements exhibit a uniform distribution. Therefore, based on the XRD test results, the composition of the NMCO-8 sample can be recorded as a trimetallic oxide Ni. x Mn 1-x Co2O4.
[0053] Figure 4 This is a transmission electron microscope (TEM) image. From... Figure 4 As can be seen, NMCO-8 particles exhibit a distinct core-shell structure: the core is a relatively dense region, while the outer layer is a porous shell with a thickness of 500-800 nm. This shell is assembled from nanoscale fine particles and has an irregular serrated surface.
[0054] Figure 5 This is a high-resolution transmission electron microscope (HRTEM) image, from... Figure 5 As can be seen, the interplanar spacing of NMCO-8 is closer to that of the cubic phase MnCo2O4. However, due to the presence of nickel occupying some lattice sites, the overall interplanar spacing of the material is slightly smaller than that of MnCo2O4, but significantly larger. This suggests that the trimetallic oxide Ni... x Mn 1-x In Co2O4, manganese occupies more structural sites than nickel.
[0055] Figure 6 The N2 adsorption-desorption isotherms and BJH pore size distribution of the NMCO-8 sample are shown below. Figure 6 As can be seen, the NMCO-8 sample exhibits a typical Type IV isotherm curve with a distinct H3-type hysteresis loop, indicating the presence of a mesoporous structure in this material. The pore size distribution curve shows that the sharp characteristic peak at 2–5 nm further confirms the presence of mesoporous channels in the NMCO-8 product; while the broad peak in the 10–100 nm range indicates the simultaneous presence of significant mesoporous and macroporous structures in the product. These results are consistent with the SEM and TEM results.
[0056] Furthermore, in an argon-filled glove box at room temperature, the black powder product prepared in Example 1 was used as the active material for assembling a CR2025 button cell for battery performance testing. The working electrode was prepared as follows: an N-methylpyrrolidone (NMP) slurry containing 70 wt% active material (NCO-2,4,6,8), 10 wt% polyvinylidene fluoride (PVDF), and 20 wt% acetylene black was uniformly coated onto the surface of a copper foil current collector, and then dried in a vacuum oven at 40°C for 12 hours. The active material loading of the working electrode was approximately 1.2 mg·cm³. -2 In the battery system, a Celgard 2400 separator is used, and the electrolyte is a mixed solvent system of 1 M LiPF6 dissolved in ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1.
[0057] The prepared CR2025 button cell was subjected to charge-discharge cycle performance and rate performance tests, and the results are as follows: Figure 7 and Figure 8 As shown. From Figure 7 It can be seen that when the NMCO-8 material sample is used as a negative electrode material for lithium-ion batteries, it exhibits a reversible capacity as high as 1008 mAh g / g at a high current density of 500 mA / g. After 1000 consecutive charge-discharge cycles, its capacity still remains above 500 mAh / g, demonstrating significant advantages in high capacity and high cycle stability. Figure 8 It can be seen that when the NMCO-8 material sample is used as a negative electrode material for lithium-ion batteries, it has excellent high-flow discharge capability and can still maintain a stable cycle capacity of more than 300mAh / g at a high rate of 10C. Therefore, the trimetallic oxide electrode material synthesized by this process can meet the battery application requirements of fast charging scenarios.
[0058] The morphology of the black powder products prepared in Examples 1 and 2, as well as Comparative Examples 1-5, was observed by scanning electron microscopy using the same method. The results are as follows: Figure 9 As shown. From Figure 9 It can be seen that the black powder products prepared in Examples 11 and 2, as well as Comparative Examples 1-5, all exhibit the morphological characteristics of nanoporous microspheres, but with slight differences in structural details. Therefore, this invention achieves a nanoporous trimetallic oxide Ni based on a simple hydrothermal reaction. x Mn 1-xControllable preparation of Co2O4. In comparison, compared with other comparative examples using different amounts of TEA, Example 1, using 8 mL of TEA, yielded nanoporous microspheres with relatively uniform morphology and size. When the amount of TEA was ≥8 mL, the morphology remained basically consistent, but the particle size tended to gradually increase. When the amount of TEA was 2–6 mL, the morphology of the product changed from micron-sized porous cubes to elliptical and spherical shapes, and the surface gradually exhibited more dense and ordered porous structural details. Therefore, it can be concluded that using 8–10 mL of TEA in this preparation process is the optimal choice for obtaining core-shell structured nanoporous microspheres with uniform structure and morphology.
[0059] The morphology and microstructure of the black powder product prepared in Comparative Example 5 were observed using field emission scanning electron microscopy (FE-SEM, JEOL JSM-7500F) and transmission electron microscopy (TEM, JEOL JEM-2100F). The elemental composition of the samples was analyzed using an energy-dispersive X-ray spectrometer (EDS) mounted on the FE-SEM and an X-ray photoelectron spectrometer (XPS, AXIS ULTRA DLD) equipped with a MgKα–AlKα dual-anode excitation source. Specific results are shown below. Figures 10-13 As shown. From Figures 10-13 As can be seen from the SEM and TEM results, Comparative Example 5 also exhibits a relatively uniform core-shell structured nanoporous microsphere morphology, although the particle size is slightly different from that of Example 1. This may be related to the interaction between the metal salt and TEA, thus proving that this invention is generalizable.
[0060] The above description is merely an exemplary embodiment of this application and does not limit the patent scope of this application. Any equivalent structural transformations made based on the technical concept of this application and the contents of the specification and drawings of this application, or direct / indirect applications in other related technical fields, are included within the patent protection scope of this application.
Claims
1. A method for preparing micro / nano core-shell structured metal oxide materials, characterized in that, include: A precursor solution is prepared by dissolving a metal source containing nickel ions, manganese ions, and cobalt ions, urea, and triethanolamine in water and mixing them. The precursor solution was subjected to a hydrothermal reaction to obtain a precursor precipitate; The precursor precipitate was subjected to heat treatment to obtain the micro / nano core-shell structured metal oxide material. The molar ratio of nickel ions, manganese ions, and cobalt ions in the metal source is 1:(0.8~1.2):(3.5~4.5). The amount of triethanolamine added is 8-10 mL per 100 mL of water; The hydrothermal reaction is carried out at a temperature of 160~200℃ for 2~4 hours. The heat treatment temperature is 500~700℃, the heating rate is 2~10℃ / minute, and the time is 4~10 hours.
2. The preparation method according to claim 1, characterized in that, The process prior to the heat treatment also includes: The precursor precipitate is then cleaned and dried.
3. A micro / nano core-shell structured metal oxide material prepared by the preparation method according to claim 1 or 2, characterized in that, The micro / nano core-shell structured metal oxide material has a core-shell structure and a hierarchical porous structure.
4. The micro / nano core-shell structured metal oxide material as described in claim 3, characterized in that, The micro / nano core-shell structured metal oxide material is a ternary metal oxide with the chemical formula Ni. x Mn 1-x Co2O4, where 0 <x<1。 5. The application of the micro / nano core-shell structured metal oxide material prepared by the preparation method according to claim 1 or 2, and the micro / nano core-shell structured metal oxide material according to claim 3 or 4 in the preparation of alkali metal ion batteries.